Benchmarking policy goals and actions for healthy food environments in Ethiopia to prevent malnutrition in all its forms using document analysis - Trübswasser, Ursula; Candel, Jeroen; Genye, Tirsit; Bossuyt, Anne; Holdsworth, Michelle; Baye, Kaleab; Talsma, Elise F. (BMJ, 2022)
Unhealthy diets resulting in overweight and obesity and diet-related non-communicable diseases are of increasing concern in Ethiopia, alongside persistent undernutrition, and have been linked to unhealthy food environments. Little is known about the policy response to unhealthy food nvironments in Ethiopia. The objective of this study was to assess how different food environment domains have been addressed in Ethiopian policy goals and action over time and how this compares with global good practice benchmarks.